Pengembangan Media Geometri Berbantuan Software Geogebra pada Mata Pelajaran Matematika Materi Koordinat untuk Mempermudah SiswaKelas V - Fitri, Nanda Yulia; Sukmawarti, Sukmawarti (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to develop Geometry media assisted by Geogebra Software in Coordinate learningwhich can facilitate teachers in the teaching and learning process and determine the effectiveness of Geogebra Media assisted by GeoGebra Software in Coordinate learning. This type of research is research and development or Research and Development (R&D),using the ADDIE Model (Analysis, Design,Development, Implementation and Evaluation). The research was carried out only up to the Development stage. The product developed is geometric media which is assessed by experts to find out whether the media is feasible or not. The type of data used in this research is descriptive qualitative data. The results of the assessment carried out by experts, namely media experts and material experts, that the geometry media and coordinate material used in Geogebra Softwareare suitable for use without any revision. The conclusion in this study is that the results of Geometry media assisted by Geogebra Software which were developed in the form of assessments from media experts and material experts showed that the media agreedand were suitable for use in the learning process.